The influence of a response format test accommodation for college students with and without disabilities. Issue 7 (2nd October 2016) - Potter, Kyle; Lewandowski, Lawrence; Spenceley, Laura
Abstract : Standardised and other multiple-choice examinations often require the use of an answer sheet with fill-in bubbles (i.e. 'bubble' or Scantron sheet). Students with disabilities causing impairments in attention, learning and/or visual-motor skill may have difficulties with multiple-choice examinations that employ such a response style. Such students may request and receive testing accommodations that intend to mitigate these impairments, such as circling responses in a test booklet, which contains both the questions and corresponding multiple-choice answers. The current study evaluated this test accommodation as compared to using a bubble sheet or Scantron on a multiple-choice vocabulary test. College students with ( n  = 25) and without ( n  = 76) disabilities completed a vocabulary test under both booklet (accommodated) and bubble sheet (standard) conditions. Results demonstrated that answering in a test booklet, a much preferred response mode, allowed students to attempt significantly more items than using a bubble sheet, improving their overall test scores. Booklet responding tends to improve overall performance, even for students without disabilities, calling into question the specificity and validity of this accommodation.